Aspek Hukum Kewenangan Pemerintah Daerah Pada Pemulihan Lingkungan Akibat Usaha Pertambangan - Wongkar, Vonny Anneke; Wewengkang, Feiby S.; Mamahit, Cobi Elisabeth Montesori (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The aim of this study is to determine local governments' authority over environmental recovery as a result of mining activity. This study employs an empirical normative research method with three approaches: legislative, conceptual, and case-based. The study's findings show that local governments' authority in environmental rehabilitation as a result of mining activities is biased since the local community is not involved. The recovery process must begin with the fulfillment of environmental permits and environmental studies, followed by planning, implementation, and supervision at the exploration, production, and post-mining stages. In the event of environmental pollution, the recovery obligation is transferred to the local mining company/business entity. It is advised that reclamation and post-mining activities be designed in such a way that they become the authority of the government and mining industry actors, with the community as directly associated partners.